IMPLEMENTATION OF ABSOLUTE LIABILITY IN ENVIRONMENTAL DISPUTE RESOLUTION IN THE PROTECTION AND MANAGEMENT FRAMEWORK IN INDONESIA - Sonny Magranta Silaban; Anna Juliarti; Irawan Harahap (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
In forest and land fire cases, the focus of evidence is not solely directed at the perpetrator's intent or fault, but rather on the link between business activities and the occurrence of environmental damage that results in ecological and social losses. The purpose of this study is to analyze the regulations for resolving environmental disputes in Indonesia and to analyze the application of strict liability in resolving environmental disputes within the framework of protection and management in Indonesia. Based on the results of the study, it is known that the regulation of environmental dispute resolution in Indonesia has been comprehensively regulated in Law Number 32 of 2009 concerning Environmental Protection and Management through settlement mechanisms outside the courts (non-litigation) and through the courts (litigation). These regulations aim to provide legal protection to communities harmed by environmental pollution and/or damage and ensure the restoration of environmental functions. In addition to regulating individual lawsuits, the UUPPLH also recognizes class action lawsuits, the right to sue environmental organizations (legal standing), and the right to sue the government as instruments for enforcing environmental law oriented towards sustainable environmental protection. The application of strict liability in environmental dispute resolution strengthens environmental legal protection as specified in Article 88 of the Environmental Management Law (UUPPLH). This principle exempts victims from the obligation to prove fault on the part of the business actor and only requires the existence of losses and a link between the activity and the resulting environmental impact. The application of strict liability reflects the implementation of the polluter pays principle and the precautionary principle in Indonesian environmental law, thereby increasing the effectiveness of law enforcement and encouraging business actors to be more responsible in environmental management.